2009
DOI: 10.1002/hed.21289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of available surgical management options for early supraglottic cancer

Abstract: Larynx-preserving surgical modalities offer comparable oncologic results with total laryngectomy in early supraglottic cancer. In addition, laser surgery has a lower incidence of complications and better functional results compared with open partial or total laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
5
34
0
4
Order By: Relevance
“…The functional results after transoral laser surgery of supraglottic carcinomas are good, permanent tracheostomy and functional laryngectomy as well as permanent PEG are rare [16], [53], [56], [57]. Ambrosch et al [16] reported about 2% permanent tracheostomies in a population of 50 patients with T3 supraglottic carcinomas.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The functional results after transoral laser surgery of supraglottic carcinomas are good, permanent tracheostomy and functional laryngectomy as well as permanent PEG are rare [16], [53], [56], [57]. Ambrosch et al [16] reported about 2% permanent tracheostomies in a population of 50 patients with T3 supraglottic carcinomas.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
“…In former times, open partial laryngectomy represented a high percentage of interventions. Today the indication of open surgery of T1 and T2 tumors of the larynx is only rarely made in western industrial nations because retrospective case series showed similar oncologic results of open partial laryngectomy and transoral laser surgery for supraglottic and glottic carcinomas but an increased perioperative morbidity of open partial resection [57], [59], [79]. In particular classic vertical partial resections are more and more rarely applied.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
“…Die postoperative Aspiration ist passager und meist nur gering ausgepr ä gt. Daher sind sekund ä re permanente Tracheotomien und Laryngektomien aus funktionellen Gr ü nden nur selten notwendig [30,150,155,158,199,215,216] . Faktoren, die wesentlich die Wiedererlangung der Schluckfunktion nach supraglottischer Larynxteilresektion, ob transzervikal oder endoskopisch durchgef ü hrt, beeinfl ussen sind: die oropharyngeale Transitzeit des Bolus, der Schluss der Atemwege am Kehlkopfeingang, die Position des Restlarynx in Relation zum Zungengrund, die Bewegung des Zungengrunds an die Rachenhinterwand und die Elevation des Restlarynx [214,217,218] .…”
Section: Funktionelle Ergebnisseunclassified
“…& Organ-preserving laser surgery in early laryngeal cancer has shown equal survival rates as radical surgery but with improved functional outcome [3]. & Some departments offer complex reconstructions with pedicled and increasingly free flaps after extensive tumor removal to maintain better functional outcome.…”
Section: Introductionmentioning
confidence: 99%